EVALUATING THE EFFECTIVENESS OF THE EDUCATIONAL COMPUTER PROGRAM "METHODS OF DIAGNOSIS OF THE FUNCTIONAL STATE OF THE HUMAN BODY" - Khomenko, P.V. (World of Medicine and Biology, 2015)
In the article the methodological and theoretical aspects of the use of information and communication technologies in the training of specialist industry "Physical education, sport and health" and verified the effectiveness of the program developed in the educational process of higher educational institutions. Develop training computer program in the unity of three components: a training block "Methods of diagnosis of the functional state of the organism in physical rehabilitation, physical culture and sport", an experimental unit and the subsystem integrated test control of knowledge.
Keywords: information and communication technologies; educational computer software; information competence